Pengaruh Stres Kerja terhadap Kinerja Petugas Operasional PT. Angkasa Pura II di Bandar Udara Internasional Husein Sastranegara Bandung - Primalia Rafa Shahira; Eny Sri Haryati (Pusat Riset dan Inovasi Nasional, 2024)
Job stress is a part of life stress that is too heavy so that it is directly related to psychological disorders and physical discomfort. Stress is a condition that can be experienced by employees as a result of work demands, time pressure, heavy workload, interpersonal conflicts, and other factors. The problem of stress can be one of the significant factors that can affect employee performance. This study aims to determine the effect of job stress on the performance of operational officers of PT Angkasa Pura II at Husein Sastranegara International Airport Bandung. This study applies a quantitative approach with 43 respondents, selected through the Non Probabilty Sampling method. Primary data collection was carried out through distributing questionnaires using a Likert scale. Data processing was carried out with the SPSS program. Data analysis was carried out by conducting validity tests, reliability tests, simple linear regression analysis, t tests, coefficient of determination tests. The results of the data analysis test obtained the significance value of the Work Stress variable (X) on the Performance of Operational Officers (Y) of 0.000> 0.05 can be interpreted that there is a significant and positive influence. When viewed from R2 between the variable Job Stress (X) on the Performance of Operational Officers (Y) it can be interpreted that the effect of Job Stress on the Performance of Operational Officers of PT Angkasa Pura II at Husein Sastranegara International Airport Bandung is 30.9% and 61.9% is influenced by variables outside this study.